2006
DOI: 10.1111/j.1440-1754.2006.00824.x
|View full text |Cite|
|
Sign up to set email alerts
|

Rapid sterilisation of cerebrospinal fluid in meningococcal meningitis: Implications for treatment duration

Abstract: Children in this study with MM had rapid sterilisation of the CSF in less than 6 h. This would support recent recommendations to reduce the duration of antibiotic therapy to 4 days. There is however, lack of long-term data on sequelae with 4 days of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
(40 reference statements)
0
5
1
2
Order By: Relevance
“…Data from children that had received serial LPs showed that by 2 h after the antibiotics were started, all CSF samples were sterile for N meningitidis , and by 4–10 h, 70% were sterile for S pneumoniae . In a study of childhood meningococcal meningitis, sterile CSF was noted in all cases that underwent an LP more than 5 h after starting parenteral antibiotics 12. In contrast, in our study in adults, we found that N meningitidis could be cultured up to 6–8 h after starting antibiotics.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Data from children that had received serial LPs showed that by 2 h after the antibiotics were started, all CSF samples were sterile for N meningitidis , and by 4–10 h, 70% were sterile for S pneumoniae . In a study of childhood meningococcal meningitis, sterile CSF was noted in all cases that underwent an LP more than 5 h after starting parenteral antibiotics 12. In contrast, in our study in adults, we found that N meningitidis could be cultured up to 6–8 h after starting antibiotics.…”
Section: Discussioncontrasting
confidence: 90%
“…Culturing the organism can yield information about antibiotic resistance, which is especially important for Streptococcus pneumoniae , or lead to contact tracing and postexposure prophylaxis, and sometimes vaccination, which are especially important for Neisseria meningitidis . Several studies in children have shown that the chances of culturing a pathogen from the cerebrospinal fluid (CSF) in bacterial meningitis are reduced, the longer the delay between starting antibiotic treatment and performing the LP 11 12. Similar data are not available for adults.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In our study only in 4.4% of cases causative organism was isolated making it difficult for deriving information related to antibiotic effect on CSF cultures. The reasons for low yield of cultures in our study are not clear but may include use of antibiotics prior to hospitalization as evident from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…CSF obtained from children with bacterial meningitis, after the initiation of antibiotics, may be negative on Gram stain and culture. 7,8 Pleocytosis with a predominance of neutrophils, elevated protein level, and a reduced concentration of CSF glucose usually persist for several days after the administration of appropriate intravenous antibiotics. 9 Some previous work suggested that antibiotic pretreatment does not affect or has only a small influence on CSF white blood cell (WBC) profiles in patients with bacterial meningitis while others found significant alteration in CSF profile.…”
mentioning
confidence: 99%
“…Prinzipiell gilt, dass die optimale Anti− biotikatherapie so lang wie nötig und so kurz wie möglich sein sollte [101]. Retrospektive Datenanalysen deuten darauf hin, dass bei Kindern mit einer Meningokokkenmeningitis eine The− rapiedauer von 3±4 Tagen ebenso effizient sein kann wie eine längerfristige Antibiotikagabe [102,103]. Ferner zeigten 2 pro− spektive, randomisierte Studien, dass bei Kindern mit einer aku− ten eitrigen Meningitis (unterschiedlicher bakterieller Genese) die 7−tägige Gabe von Ceftriaxon ebenso wirksam war wie eine 10−tägige Ceftriaxongabe [104,105].…”
unclassified